Computer network security peep-proof screen device - XIAO HONGWEI; DAI BOTAO; HUANG XINXIA; ZHOU XIANJING (2023)
The utility model relates to the technical field of computer peep prevention, in particular to a computer network security peep-proof screen device which comprises two fixing mechanisms, the two fixing mechanisms are distributed left and right and are not in contact, the front ends of the two fixing mechanisms are fixedly connected with a peep-proof mechanism together, the two fixing mechanisms are fixedly installed at the upper end of a displayer together, and the peep-proof mechanism is fixedly connected with the computer network security peep-proof screen device. A display screen is arranged at the front end of the displayer, a supporting frame is fixedly connected to the lower portion of the rear end of the displayer, the peep-proof mechanism comprises an automatic winding drum, a peep-proof film is fixedly wound in the automatic winding drum, two hooks are fixedly connected to the output end of the peep-proof film, and the two hooks are distributed left and right and do not make contact with each other.